AN INTERACTIVE EDUCATIONAL SYSTEM FOR LOGISTICS TRAINING BASED ON ROBOTICS - Buronova Gulnora; Mekhrangiz, Halimova (Journal of Higher Education and Academic Advancement, 2025)
Objective: This study aims to explore how robotics can be integrated into logistics education to create an interactive learning system that enhances students’ professional and technical skills, addressing the growing demand for smart supply chain solutions and the need for innovative training methods. Method: A practice-oriented approach was employed, involving the design of a robotics-assisted curriculum for logistics students, incorporating warehouse automation models, robotic simulators, and interactive digital platforms to support hands-on learning, with data collected through classroom observations, student feedback, and performance evaluations, emphasizing active participation, problem-solving tasks, and collaborative learning scenarios reflecting real-world supply chain processes. Result: The findings indicate that robotics-assisted learning significantly improved students’ ability to understand logistics workflows, manage automated systems, and apply theoretical knowledge in practical settings, while students also demonstrated higher engagement, stronger motivation, and improved teamwork skills compared to traditional lecture-based methods. Novelty: Integrating robotics into logistics education offers a promising framework for developing future-ready specialists in supply chain management, supporting both technical proficiency and critical thinking, and enabling learners to adapt to emerging trends in smart logistics and contribute effectively to the development of intelligent supply chains.